Intellectual property infringements due to R&D abroad? A comparative analysis between firms with international and domestic R&D activities - Anja Schmiele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper aims at analysing the risk of intellectual property (IP) infringements by competitors from abroad and in particular whether this risk is higher for international innovating firms. We distinguish three different types of IP infringements from abroad: the usage of firms' technical inventions, product piracy and copying of corporate names and designs. Our analysis rests on the German data from the Europe-wide Community Innovation Survey (CIS). We use a unique data set of about 900 observations which are retrieved from two survey waves. While the earlier wave contains information about international and domestic innovation activities the later wave reports IP infringements. In a second analysis, the likelihood of infringements from innovation host countries and no innovation host countries abroad is examined. Before the empirical analysis, an explorative study has been carried out in China with interviews of German firms with innovation activities in China and with a legal advisor for small and medium sized German enterprises. The results show that firms with international R&D activities are increasing their chances to lose technological knowledge to their local competitors abroad. R&D activities in countries with weak intellectual property rights increase the risk for all types of infringement. Infringements by competitors from the host country are driven by the production of innovations in this country. Export intensity is the major driver of infringements from no innovation host countries. R&D activities in China and North America also increase the risk of an infringement. However, firms that innovate only in their home country experience significantly more product piracy cases than internationally innovating firms.
Keywords: O32; O34; F23; 330; R&D; innovation; internationalisation; intellectual property; infringement; Imitationswettbewerb; Innovationswettbewerb; Produktpiraterie; Immaterialgüterrechte; Industrielle Forschung; Globalisierung; Multinationales Unternehmen; Deutsch; Deutschland; Welt